A Maurer's cleft-associated Plasmodium falciparum membrane-associated histidine-rich protein peptide specifically interacts with the erythrocyte membrane (2009)
The membrane-associated histidine-rich protein-1 (MAHRP-1) is a Maurer's cleft-resident molecule that has been recently described as an important protein for the trafficking of PfEMP-1 to infected erythrocyte membrane, a major virulence factor. We have studied the specific interactions between 20-mer-long synthetic peptides spanning the complete MAHRP-1 sequence and erythrocytes. A high-activity binding peptide (HABP) with saturable binding to a 46-kDa erythrocyte membrane protein was identified and its binding was affected by chymotrypsin treatment. Random coil and ?-helical features were found in the HABP's structure. Our results suggest that MAHRP-1 specifically interacts with erythrocyte membrane through a 20-mer-long amino acid region, raising questions about this region's potential as a therapeutic target against malaria. © 2009 Elsevier Inc. All rights reserved.